2015
DOI: 10.1007/s13730-015-0202-1
|View full text |Cite
|
Sign up to set email alerts
|

De novo papillary carcinoma in a renal allograft: the pros and cons of immunosuppression

Abstract: We present a case of a multifocal kidney transplant renal cell carcinoma in a 35-year-old lady, presenting 16 years after kidney transplantation, diagnosed during investigation of recurrent urinary tract infections. The patient underwent a graft nephrectomy and subsequently maintained on haemodialysis. She remained disease-free after 4 years of surveillance and thus reactivated on the transplant list. This case reinforces the fact that immunosuppressive therapy has made kidney transplantation possible; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Despite the possible benefits expected from routine non-oncologic transplant nephrectomy, routine excision is not the standard, because it is a technically demanding procedure [ 13 , 14 ]. Even without the presence of malignancy, transplant radical nephrectomy of a failed allograft is associated with improvement in hematological, biochemical, and clinical parameters, such as erythropoietin (EPO) resistance index, serum levels of albumin, prealbumin, ferritin, fibrinogen, c-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) [ 15 , 16 ]. Studies have shown that the removal of the patient’s transplanted kidney at the time the patient has progressed to requiring dialysis is independently associated with increased survival [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the possible benefits expected from routine non-oncologic transplant nephrectomy, routine excision is not the standard, because it is a technically demanding procedure [ 13 , 14 ]. Even without the presence of malignancy, transplant radical nephrectomy of a failed allograft is associated with improvement in hematological, biochemical, and clinical parameters, such as erythropoietin (EPO) resistance index, serum levels of albumin, prealbumin, ferritin, fibrinogen, c-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) [ 15 , 16 ]. Studies have shown that the removal of the patient’s transplanted kidney at the time the patient has progressed to requiring dialysis is independently associated with increased survival [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these concerns are not clinically relevant in the case of renal allograft malignancies because those patients nevertheless would not be candidates for subsequent transplantation without transplant radical nephrectomy or nephrouretectomy. Systemic therapies are often more challenging for malignancies of renal allograft compared to kidney cancers in native functioning kidneys, and often are not ideal treatment options [ 16 ]. Extirpative surgery for malignancies of the renal allograft can benefit these patients in various ways by removing both the malignancy and the failed allograft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of renal cell carcinoma in allografts is approximately 0.2% in the transplanted kidney population. The increasing survival of these patients is believed to be a factor in the rising incidence rate of this disease, 1 as well as the immunosuppression therapy, 2 , 3 , 4 , 5 especially the cyclosporine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, calcineurin inhibitors (CNIs) have been shown to play a role in the proliferation of malignant cells by increasing the levels of VEGF and TGF-beta-1. 4 A lower CNI dose may increase the risk of acute rejection, although it reduces the risk of cancer. Alternatives for CNIs include mTOR inhibitors, which reduce the risk of de novo tumors, but carry a higher risk of transplant rejection.…”
Section: Discussionmentioning
confidence: 99%